Detection of Enterovirus, Herpes Simplex, Varicella Zoster, Epstein‐Barr and Cytomegalovirus in cerebrospinal fluid in meningitis patients in Iran. Issue 7 (21st June 2021) - Tavakolian, Shaian; Goudarzi, Hossein; Eslami, Gita; Darazam, Ilad Alavi; Dehghan, Golnaz; Faghihloo, Ebrahim
Abstract: Background: Despite medical advances, central nervous system (CNS) diseases put a pressure on the health care system. A number of risk factors, especially infectious agents can accelerate the progression of meningitis. As viruses probably account for most cases of meningitis, the diagnosis of them can reduce antibiotic prescriptions. Among various types of infectious diseases, the relationship between two important virus families, including Picornaviridae and Herpesviridae, and meningitis has attracted attraction. Methods: In this study, one hundred and two samples were collected from patients who experienced symptoms, such as the loss of consciousness, seizures, muscle weakness, fever, headache, rash, and severe dementia, between November 2018 and September 2019. After RNA and DNA extraction, the prevalence of Enterovirus (EV), Cytomegalovirus (CMV), Epstein–Barr virus (EBV), Herpes simplex virus type 1 (HSV‐1), Herpes simplex virus type 2 (HSV‐2), and Varicella zoster virus (VZV) was evaluated using PCR, multiplex PCR, and nested PCR. Results: Results indicated that there were two VZV DNA‐positive specimens, while six and five samples were infected with HSV‐1 and EBV, respectively. Conclusion: We reported that the prevalence of EBV, HSV‐1, and VZV in patients, suffering from meningitis cannot be ignored; however, further investigation is needed. Abstract : After collecting samples and extracting RNA and DNA, the prevalence of Enterovirus (EV), Cytomegalovirus (CMV), Epstein‐Barr virus (EBV), Herpes simplex virus type 1 (HSV‐1), Herpes simplex virus type 2 (HSV‐2), and Varicella zoster virus (VZV) was evaluated using PCR, multiplex PCR, and nested PCR.